(untitled) (American Journal of Pedagogical and Educational Research, 2023)
A method of prosthetics with partially removable prostheses fixed with a telescopic or double crown is described. The design and functional features of the crown are described. Indications and contraindications to the use of this type of prosthetics are presented. The nuances of its manufacture are discussed. The historical stages of the use of double crowns are described. Recommendations on the use of telescopic fixation systems are also given.